Mobility Barriers and the Speed of Market Selection - Werner Hölzl (Austrian Institute of Economic Research (WIFO), 2012)
This paper studies the influence of mobility barriers on industry evolution using the stylised pure selection model developed by Metcalfe. It is shown that mobility barriers influence industry dynamics by reducing the speed of competitive selection. Based on the theoretical model, we argue that mobility barriers should lead to a reduction of market share reallocation dynamics in models that use replicator dynamics. We then test this prediction empirically, finding that industries with high mobility barriers have a larger share of stable firms that grow or decline only marginally, compared to industries with low mobility barriers. This has important implications for the interpretation of productivity decompositions. Our empirical results show that higher mobility barriers result in a lower contribution of reallocation to aggregate productivity growth in Austrian manufacturing industries.
Keywords: 330; Intensity of competition; mobility barriers; sunk costs; selection dynamics; firm growth; reallocation; Wettbewerb; Marktgröße; Markteintritt; Sunk Costs; Unternehmenswachstum; Produktivität; Industrie; Österreich